EVALUATION OF A COMPREHENSIVE EULERIAN AIR-QUALITY MODEL WITH MULTIPLE CHEMICAL-SPECIES MEASUREMENTS USING PRINCIPAL COMPONENT ANALYSIS - Li, S. M.; Anlauf, K. G.; Wiebe, H. A.; Bottenheim, J. W.; PUCKETT, KJ (ATMOSPHERIC ENVIRONMENT, 1994)
Using a principal component analysis technique and data on atmospheric gases and aerosols at a rural site in Ontario, Canada from the Eulerian model evaluation field study (EMEFS), the Eulerian acid deposition and oxidant model (ADOM) is evaluated. Seventy-nine and 76% of the variances in the data and model output, respectively, are explained by three principal components. They are a chemically aged/transported component, a diurnal cycle component, and an area emission component, all characterized by their ratios of gases and temporal variation patterns. The ADOM component contributions to sulphur species are in general agreement with the EMEFS components, but with notable differences for key photochemical species including O-3. The temporal variations of the ADOM components are close to those of the EMEFS components. The EMEFS chemically aged/transported component shows a high degree of photochemical processing, with the ratios [NOx]/[TNOy]=0.3 and [O-3]/([TNOy]-[NOx])=9+/-1. The corresponding ADOM component predicts lower [NOx]/[TNOy] and [O-3]/([TNOy]-[NOx]) ratios, probably caused by a chemical mechanism in the model that is too fast, and lower contributions to O-3, NO2, TNO3, PAN, TNOy, and HCHO, probably caused by model grid dilution or lower model emissions. The EMEFS diurnal component owes its variance to the daily photochemistry and nighttime dry deposition of the chemical species. In comparison, the matching ADOM component underpredicts the ratio [O-3]/([TNOy]-[NOx]) and the NO2 consumption and O-3 production but overpredicts the contributions to the other species. The EMEFS emission component represents emissions from local/regional area sources. The corresponding ADOM component underpredicts TNOy by 44% and the fraction of TNOy as NOx compared to the EMEFS component, suggesting that the model has lower emissions of NOx and a photochemical mechanism that converts NOx faster than indicated by the EMEFS results.